Stakes Matter in Ultimatum Games - Steffen Andersen; Seda Ertaç; Uri Gneezy; Moshe Hoffman; John A. List (Copenhagen Business School (CBS), Department of Economics, 2011)
The canonical bargaining game in economics is the ultimatum game, played by tens of thousands of students around the world over the past three decades. In the ultimatum game, first studied by Werner Guth, Rolf Schmittberger, and Bernd Schwarze (1982), the “proposer” proposes how to split a pie between herself and a “responder.” Then the responder decides whether to accept or reject this proposal. If the responder accepts, then the proposal is implemented; otherwise, both players receive nothing. For players motivated purely by monetary considerations, the standard subgame-perfect equilibrium solution implies that the proposer receives almost all of the money. In this manner, the ultimatum game represents a stylized glimpse into the underpinnings of decision-making at the heart of economics. For instance, a monopolist setting a price, a monopsonist setting a wage, or more generally any bargaining situation that has a take it or leave it element.
hdl:10398/8244
Keywords: C70; D40; 330; game theory; decision-making; price theory